Enhanced photo-responsiveness in a photoswitchable system model: emergent hormetic catalysis. Issue 20 (5th May 2017) - Micheau, J.-C.; Coudret, C.
Abstract : Numerical simulations of a continuously illuminated photoswitchable catalytic system unveil photohormesis: how profitable can be an incomplete but dynamic photoswitching. Abstract : Michaelis Menten catalysis by a T-photochromic system has been analyzed numerically. Using an appropriate set of rate constants and quantum yields, we have evidenced an enhanced photo-responsiveness at a medium light intensity: the plot of the initial rate vs. light intensity is bell-shaped. This emergent phenomenon can be qualified as hormetic catalysis. The analysis of the chemical flows shows that a directional rotation occurs within the cyclic scheme. Non equilibrium conditions are provided by two independent sources: the chemical energy dissipation from the irreversible exergonic reaction and the steady transformation of light into heat by T-photochromism. A literature survey, showing that most of the required kinetic features are not so rare, let us anticipate its practical feasibility.